Phonics-Guided Reading for Students’ Pronunciation Accuracy - Wiwik Andriyani Rahmat; Muhammad Hifdil Islam; Feri Ferdiyanto (Journal of English Language and Education, 2026)
Pronunciation remains a major challenge for young EFL learners, particularly in rural classrooms where students have limited exposure to English and often rely on first-language pronunciation patterns. This research explored the implementation of phonics-guided reading in supporting students’ pronunciation accuracy at MI Nur Hayatul Islam, Probolinggo, Indonesia. Conducted over four weeks, the study involved one English teacher and fifteen fifth-grade students. A qualitative descriptive approach was employed, with data collected through classroom observations, semi-structured interviews, and documentation. The findings revealed that phonics-guided reading helped students recognize sound–letter relationships more systematically and reduced their tendency to pronounce English words using Indonesian spelling patterns. Students also became more active and confident during reading activities. However, several challenges were identified, including limited instructional media, difficulties in distinguishing unfamiliar English sounds, and the teacher’s limited experience in applying phonics instruction consistently. These findings suggest that phonics-guided reading can serve as a supportive approach for improving pronunciation awareness and classroom engagement among elementary EFL learners in rural contexts.